School children's acceptability of mango flavored soybean curd - Francisco, Kenda Vergel B. (2000.)
The extent of consumer's acceptability to mango flavored soybean curd was determined.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Curd; Tofu